Konsep Pendidikan Esensialisme dalam Pembentukan Karakter Siswa pada Mata Pelajaran Pendidikan Agama Islam - Almi Novita; M. Yunus Abu Bakar (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2021)
Essentialism educational philosophy is one of the traditional educational philosophies which views that the values in education should be based on clear and long-lasting values, then the existing education in a country can remain stable and focused.The purpose of the essentialism educational philosophy is to improve the character of society through existing cultural heritage, so that later students can contribute to improving people's lives in the face of changing times that can kill the character values of students.The philosophy of essentialism also aims to form a happy person in the world and the hereafter through values of virtue (moral, character and morals) that are embedded in students, because school, teachers and students are the key to developing an advanced nation, and play a very important role for character building in the school and communities. This article seeks to conceptualize the goals of the philosophy of essentialism, namely to form a happy person in the world and the hereafter which includes science, art and all things that can move the human will through character building and the importance of the role of Islamic religious education teachers in shaping the character of students in schools and society.